Manufacturing of mesoscale non-assembly mechanism with water-soluble support in projection stereolithography process. (6th January 2023) - Deng, Xinghong; Zhang, Guangyu; Yu, Zhongwei; Shao, Guangbin; Li, Longqiu
Abstract: Additive manufacturing (AM) excels at building complex three-dimensional objects. With the help of support methods, macroscale non-assembly mechanisms can be built in a single step, eliminating complex and time-consuming assembly process. However, mesoscale non-assembly mechanisms built by AM are scarce for the lack of appropriate support methods. Projection stereolithography (PSL) is most fitted to manufacture mesoscale non-assembly mechanisms for its high resolution and high speed. Clearances in non-assembly mechanisms usually appear with internal overhang characteristic, requiring supports to be built successfully. However, traditional support structure in stereolithography cannot be fitted into these small internal gaps to achieve small clearances, which in turn prevents traditional stereolithography from fabricating mesoscale non-assembly mechanisms. A novel water-soluble support method is presented to overcome this restriction by incorporating water-soluble resin as support via custom-built multi-material PSL process. Internal overhangs and fragile overhangs can be built with fast support removal in mild release conditions. Mesoscale non-assembly mechanism with tight clearances is successfully fabricated. Material design, process parameters and approach to control material cross-contamination of this method are described. This support method may facilitate building functional mesoscale multi-material non-assembly mechanisms for miniaturized robotic applications.